Collaborative Quizzes: Impact on Student Performance and Attendance. (April 2019) - Petrunich-Rutherford, Maureen L.; Daniel, Frances
The current study investigated whether collaborative quizzing impacted quiz performance, overall grades, exam grades, pass/fail rates, and attendance in upper-level psychology courses. Students enrolled in two sections of upper-level psychology courses completed collaborative quizzes, whereas students enrolled in two noncollaborative sections completed quizzes individually. Students enrolled in the collaborative classes maintained quiz performance from beginning to end of the semester, whereas students enrolled in the noncollaborative classes demonstrated a general decline in quiz grades. There was also a slight increase in overall course grades for students enrolled in collaborative compared to noncollaborative classes; however, there was no difference in exam grades, pass/fail rates, and attendance between the collaborative and noncollaborative classes. Collaborative quizzes may encourage a deeper understanding of course material and/or encourage students to come prepared for the group quiz activities.